Wealth Tax as an Alternative Fiscal Instrument: A Systematic Literature Review of Its Potential to Reduce the Gini Coefficient and Increase the Taxto-GDP Ratio Toward Indonesia Emas 2045 - Arief Hidayat Adam; Radhi Abdul Halim (Journal Research of Social Science, Economics, and Management, 2026)
This study aimed to analyze the potential of wealth tax as an alternative fiscal instrument to support reductions in the Gini coefficient and increases in the tax ratio within the context of the Indonesia Emas 2045 agenda. The study employed a qualitative approach through a systematic literature review using the Scopus database as the primary source. Searches conducted for the 2015–2025 period yielded 599 initial records. After removing duplicates and conducting screening based on publication year, journal quality, abstract completeness, relevance, and full-text accessibility, a total of 117 studies from Scopus and seven supporting studies from other sources were included in the final synthesis. Data were analyzed descriptively and thematically, focusing on distributional impacts, revenue capacity, behavioral responses, administrative challenges, asset valuation, and political considerations. The synthesis results indicated that wealth taxes have the potential to reduce wealth concentration and strengthen fiscal system progressivity; however, their effects on the Gini coefficient depend on the scope of the tax base, thresholds, tax rates, exemptions, revenue utilization, and taxpayer responses. Their contribution to the tax ratio is also not automatic, as it is influenced by administrative costs, capital mobility, tax avoidance practices, and the ability of authorities to identify and assess taxable assets. The literature emphasized the importance of asset registries, third-party reporting, information exchange mechanisms, beneficial ownership identification, valuation guidelines, and risk-based supervision. For Indonesia, wealth taxes are more appropriately positioned as part of a broader fiscal reform strategy rather than as a standalone instrument.